The application of microwave and ultrasound technologies for extracting collagen from European plaice by-products - Kendler, Sophie; Kobbenes, Sine Marie Moen; Jakobsen, Anita Nordeng; Mukhatov, Kirill; Lerfall, Jørgen (Frontiers in Sustainable Food Systems, 2023)
This study’s main aim was to utilize green extraction protocols to recover collagen from by-products originating from European plaice. Moreover, the objective was to evaluate pre-treatments, the composition of the up-cycled product as well as to identify the most promising by-product fraction. Microwave (MAE) and ultrasound-assisted extractions (UAE) were performed on untreated, pre-treated (salt-washed or enzymatic hydrolysis) fractions of backbones, skins, and heads. Both MAE and UAE were performed for 15 and 35 min. After pre-treatment and extraction, the quality and yield of products were evaluated. Protein and collagen concentration, as well as amino acid profiles, were measured. Skins deliver significantly higher yields of collagen and protein than heads and backbones (p < 0.05). Enzymatic hydrolysis resulted in the highest collagen yields for skins (77%), while salt-washing gave the highest results for backbones (43%) and heads (41%) regardless of extraction method and time. Total and free amino acid profiles differed between the three fractions, with backbones and heads showing overall more similarity in composition compared to skins. The study showed that MAE and UAE technologies are suitable for generating collagen from marine by-products. Additional research is recommended to optimize pre-treatment and extraction for skin, as most promising collagen supplier.